Lack of anti-TNF drugs levels in fistula tissue – a reason for nonresponse in Crohn's perianal fistulating disease?. Issue 1 (January 2022) - Adegbola, Samuel O.; Sarafian, Magali; Sahnan, Kapil; Pechlivanis, Alexandros; Phillips, Robin K.S.; Warusavitarne, Janindra; Faiz, Omar; Haddow, James; Knowles, Charles; Tozer, Phil; Holmes, Elaine; Hart, Ailsa
Abstract : Introduction: Anti-TNF therapy is recommended as treatment for patients with Crohn´s perianal fistulas. However, a significant proportion of patients have a sub-optimal response to anti-TNF therapy. Higher serum levels of anti-TNF agents have been associated with improved outcomes in perianal Crohn's disease. Currently, it is unknown whether anti-TNF agent levels can be detected in tissue from fistula tracts themselves and whether this is associated with response. Aims and methods: We undertook a pilot study to measure fistula tissue levels of anti-TNF medication (infliximab and adalimumab). We used a previously validated targeted proteomic technique, employing ultraperformance liquid chromatography-mass spectrometry, to detect/quantify anti-TNF drugs. Biopsies were obtained from fistula tracts of patients with Crohn's disease on maintenance treatment; with idiopathic (cryptoglandular) fistula tissues used as negative controls as well as positive controls (by spiking the latter tissues with anti-TNF drugs). Results: Tissue was sampled from the fistula tracts of seven patients with Crohn's perianal disease (five patients were on adalimumab and two patients were on infliximab). The anti-TNF drugs, infliximab and adalimumab, were not detected in fistula samples from any of the Crohn's patients despite detection in 'spiked' positive control samples. Conclusion: Absence of detection of the anti-TNF drugs in fistula tissue raises the question on the role of tissue penetrance of anti-TNF drugs in response to therapy. Further work is required in a larger number of patients to validate the findings observed and investigate if any correlation exists between tissue and serum levels of anti-TNF and clinical outcome. Summary: Predicting response in Crohn's fistula patients on biologic therapy is difficult with no reliable biomarkers. This pilot study uses targeted proteomics to investigate the potential role of tissue drug levels in acting as a biomarker of treatment response. Abstract : Supplemental Digital Content is available in the text.